Prediction of Large‐for‐Gestational‐Age Neonates by Different Growth Standards. (29th August 2020) - Duncan, Jose R.; Odibo, Linda; Hoover, Elizabeth A.; Odibo, Anthony O.
Abstract : Objective: Compare the accuracy of the Hadlock, the NICHD, and the Fetal Medicine Foundation (FMF) charts to detect large‐for‐gestational‐age (LGA) and adverse neonatal outcomes (as a secondary outcome). Methods: This is a secondary analysis from a prospective study that included singleton non‐anomalous gestations with growth ultrasound at 26–36 weeks. LGA was suspected with estimated fetal weight > 90 th percentile by the NICHD, FMF, and Hadlock charts. LGA was diagnosed with birth weight > 90 th percentile. We tested the performance of these charts to detect LGA and adverse neonatal outcomes (neonatal intensive care unit admission, Ph < 7.1, Apgar <7 at 5 minutes, seizures, and neonatal death) by calculating the area under the curve, sensitivity, specificity, positive predictive value, and negative predictive value. Results: Of 1054 pregnancies, 123 neonates (12%) developed LGA. LGA was suspected in 58 (5.5%) by Hadlock, 229 (21.7%) by NICHD standard, and 231 (22%) by FMF chart. The NICHD standard (AUC: .79; 95% CI: .75–.83 vs. AUC .64; 95%CI: .6–.68; p = < .001) and FMF chart (AUC: .81 95% CI: .77–.85 vs. AUC .64; 95%CI: .6–.68; p = < .001) were more accurate than Hadlock. The FMF and NICHD had higher sensitivity (77.2 vs. 72.4 vs. 30.1%) but Hadlock had higher specificity for LGA (97.5 vs. 88.5 vs. 85.4%). All standards were poor predictors for adverse neonatal outcomes. Conclusions: The NICHD and the FMF standards may increase the detection rate of LGA in comparison to the Hadlock chart. However, this may increase obstetrical interventions. Abstract : Access the CME test here and search by article title.